[INCREMENT]9-Tetrahydrocannabinol discriminative stimulus effects of AM2201 and related aminoalkylindole analogs in rats. Issue 2 (April 2016) - Järbe, Torbjörn U.C.; Gifford, Roger S.; Zvonok, Alexander; Makriyannis, Alexandros
Abstract : The recent recreational use of synthetic cannabinoid ligands, collectively referred to as 'Spice', has raised concerns about their safety and possible differences in their biological effect(s) from marijuana/Δ 9 -tetrahydrocannabinol (THC). AM2201, a highly efficacious, potent cannabinoid receptor 1 (CB1 R) agonist, is a recently detected compound in 'Spice' preparations. Furthermore, structural analogs of AM2201 are now being found in 'Spice'. The present studies were conducted to investigate their Δ 9 -THC-like effects using drug (Δ 9 -THC) discrimination in rats. Results show that the tested compounds were potent cannabinergics that generalized to the response to Δ 9 -THC, with AM2201 being most potent, exhibiting a 14-fold potency difference over Δ 9 -THC. The other analogs were between 2.5-fold and 4-fold more potent than THC. Surmountable antagonism of AM2201 with the selective CB1 R antagonist/inverse agonist rimonabant also established that the discrimination is CB1 R dependent. Time-course data reveal that AM2201 likely peaks rapidly with an in-vivo functional half-life of only 60 min. The present data confirm and extend previous observations regarding Δ 9 -THC-like effects of 'Spice' components.